Epicardial high-resolution mapping of advanced interatrial block: Relating ECG, conduction abnormalities and excitation patterns - Ramdat Misier, Nawin L.; van Schie, Mathijs S.; Li, Chunsheng; Oei, Frans B. S.; van Schaagen, Frank R. N.; Knops, Paul; Taverne, Yannick J. H. J.; de Groot, Natasja M. S. (Frontiers in Cardiovascular Medicine, 2023)
Background: Impairment of conduction across Bachmann’s Bundle (BB) may cause advanced interatrial block (a-IAB), which in turn is associated with development of atrial fibrillation. However, the exact relation between a complete transverse line of conduction block (CB) across BB and the presence of a-IAB has not been studied. Objective: The aims of this study are to determine whether 1) a complete transversal line of CB across BB established by high resolution mapping correlates with a-IAB on the surface ECG, 2) conduction abnormalities at the right and left atria correlate with a-IAB and 3) excitation patterns are associated with ECG characteristics of a-IAB. Methods: We included 40 patients in whom epicardial mapping revealed a complete transverse line of CB across BB. Pre-operative ECGs and post-operative telemetry were assessed for the presence of (a)typical a-IAB and de novo early post-operative AF (EPOAF), respectively. Total atrial excitation time (TAET) and RA-LA delay were calculated. Entry site and trajectory of the main sinus rhythm wavefront at the pulmonary vein area (PVA) were assessed. Results: Thirteen patients were classified as a-IAB (32.5%). In the entire atria and BB there were no differences in conduction disorders, though patients with a-IAB had an increased TAET and longer RA-LA delay compared to patients without a-IAB (90.0±21.9ms vs. 74.9±13.0ms, p=0.017; 160.0±27.0ms vs. 136.0±24.1ms, p=0.012, respectively). Patients with typical a-IAB solely had caudocranial activation of the PVA, without additional cranial entry sites. Prevalence of de novo EPOAF was 69.2% and was similar between patients with and without a-IAB. Conclusions: A transverse line of CB across BB partly explains the ECG characteristics of a-IAB. We found atrial excitation patterns underlying the ECG characteristics of both atypical and typical a-IAB. Regardless of the presence of a-IAB, the clinical impact of a complete transverse line of CB across BB was reflected by a high incidence of de novo EPOAF.